OpenSSL Bellcore's Protection Helps Fault Attack - Carre, Sebastien; Desjardins, Matthieu; Facon, Adrien; Guilley, Sylvain (2018 21st Euromicro Conference on Digital System Design (DSD), 2018)
Faults in software implementations target both data and instructions at different locations. Bellcore attack is a well-known fault attack that is able to break CRT-RSA. In response, cryptographic libraries such as OpenSSL are designed with protections. In this paper, we show two new fault locations on OpenSSL implementation of the CRT-RSA signature that restore the Bellcore attack and break OpenSSL protection against it. Quite surprisingly, one of the fault we found is made possible because of the existence of such protection.